Biodiversity of epiphytic lichen at the bodogol nature conservation education center, sukabumi, west java - Diana Vivanti Sigit; Ammar Zain; Haifa Murisa; Khansa Shafa Kamila; Nur Alfi Ramadhanty; Risa Aulia Mahaqi; Rizhal Hendi Ristanto (STKIP Persada Khatulistiwa Sintang, 2022)
The Bodogol Education and Nature Conservation Center (PPKA) area is a representative area for lowland mountain tropical forest ecosystems on the island of Java so that the biodiversity in this area is quite high. The purpose of this study was to determine the diversity of lichens found in the Rasamala and Cikaweni lines of PPKA Bodogol, Sukabumi, West Java. Biodiversity research is important because of the presence of lichens as part of biodiversity that is beneficial to the ecosystem. The research method used is descriptive with exploratory techniques. Determination of trees that contain lichens is done by using purposive sampling technique. The results showed that in both pathways, lichens with crustose talus type dominated. On the Rasamala Line, 7 types of lichens were found, while on the Cikaweni Line, 5 types of lichens were found. The species diversity (H') of lichens in the Rasamala pathway was 1.51 while in the Cikaweni route it was 1.18. So based on the Shannon-Wienner formula, the biodiversity in the Rasamala and Cikaweni trails is in the medium category.